2021
DOI: 10.3390/ijms22031326
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin as a Potential Biomarker for Pregnancy Disorders

Abstract: Adiponectin is an adipocyte-derived hormone that plays a critical role in energy homeostasis, mainly attributed to its insulin-sensitizing properties. Accumulating studies have reported that adiponectin concentrations are decreased during metabolic diseases, such as obesity and type 2 diabetes, with an emerging body of evidence providing support for its use as a biomarker for pregnancy complications. The identification of maternal factors that could predict the outcome of compromised pregnancies could act as v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 139 publications
0
18
0
2
Order By: Relevance
“…11 MetS is mainly comprised of obesity according to IDF 2005, whichin turn is related to low levels of serum adiponectin. 2,12,13 It was expected that serum adiponectin levels were low in obese (≥30 kg/m²), but it could not be proved in this study.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…11 MetS is mainly comprised of obesity according to IDF 2005, whichin turn is related to low levels of serum adiponectin. 2,12,13 It was expected that serum adiponectin levels were low in obese (≥30 kg/m²), but it could not be proved in this study.…”
Section: Discussionmentioning
confidence: 65%
“…Apart from the effects of obesity and diabetes on adiponectin levels, pregnancy itself can lead to a decline in adiponectin levels due to gestational weight gain and normal hormonal changes leading to insulin resistance. 2 Similarly, low HDL levels and high TAG levels could be a part of normal physiological changes of pregnancy. 7 But as the adiponectin levels were low only in diabetic group, and HbA1c and HDL levels showed their effect on adiponectin levels, we could assume that merely pregnancy was not a predictor of adiponectin levels, and MetS had definitely played a role in decline of adiponectin levels in our study group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have studied the association between adiponectin and preeclampsia and found conflicting results. Most studies report an increase of adiponectin in the third trimester of gestation in patients with preeclampsia compared to control ( Pérez-Pérez et al, 2020 ; Pheiffer et al, 2021 ; Lara-Barea et al, 2022 ), while others found the Other adipokines such as resistin, visfatin and vaspin in gestational diabetes and preeclampsia have been described but their physiological role has yet to be established and work has been more descriptive regarding these other adipokines ( Miehle et al, 2012 ). In pregnant women plasma levels of resistin are elevated compared to non-pregnant women, however in gestational diabetes there are inconsistent data in the literature with some studies demonstrating elevation of resistin while others found decreased levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of leptin stimulating IR and the inhibitory role of adiponectin have been emphasized [ 45 , 46 , 47 , 48 , 49 , 50 ]. The pathogenesis of GDM also takes into account the participation of less known molecules such as galectins, growth differentiation factor-15, chemerin, omentin-1, osteocalcin, resistin, visfatin, vaspin, irisin, apelin, Fatty Acid-Binding Protein 4 (FABP4), fibroblast growth factor 21, lipocalin-2, fetuin-A and zonulin [ 43 , 44 , 46 , 51 , 52 , 53 , 54 , 55 ]. IR is seen in GDM patients, as well as in impaired insulin secretion due to a defect in pancreatic-cell function [ 33 , 37 , 56 ].…”
Section: Pregnancy As a Window For The Development Of Metabolic Diseasesmentioning
confidence: 99%